2006
DOI: 10.1177/0363546506288678
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Ultrasound as a Selection Tool for Reducing Achilles Tendon Reruptures

Abstract: Reduction of rerupture and surgery risks may be possible using dynamic ultrasound case selection. Further studies are needed to show whether functional results are the same with surgical and nonsurgical treatment when dynamic ultrasound criteria are used for case selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Successful non-operative treatment relies on apposition of the ruptured tendon ends, which can be assessed during ultrasound in equinus and dorsiflexion. Kotnis et al (2006) successfully used dynamic ultrasound case selection of 125 patients; 58 patients with tendon gaps <5 mm in equinus were treated nonoperatively and 67 with gaps greater than 5 mm treated operatively. The authors concluded that patients with demonstrable apposition of ruptured ends will have similar re-rupture rates treated conservatively to those managed operatively.…”
Section: Investigationsmentioning
confidence: 99%
“…Successful non-operative treatment relies on apposition of the ruptured tendon ends, which can be assessed during ultrasound in equinus and dorsiflexion. Kotnis et al (2006) successfully used dynamic ultrasound case selection of 125 patients; 58 patients with tendon gaps <5 mm in equinus were treated nonoperatively and 67 with gaps greater than 5 mm treated operatively. The authors concluded that patients with demonstrable apposition of ruptured ends will have similar re-rupture rates treated conservatively to those managed operatively.…”
Section: Investigationsmentioning
confidence: 99%
“…In some series on nonoperative AT rupture, treatment measuring tendon gap adaptation in plantar flexion by ultrasound is claimed to reduce rerupture risk; only patients without tendon gap in plantar flexion are considered for nonoperative therapy. 6,10 But there is no proper randomized trial on surgical versus nonoperative treatment in patients with AT rupture with no tendon gap at ultrasound investigation. For those without rerupture, functional bracing appears to produce good results according to Leppilahti outcome scores.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound examination of the Achilles tendon is performed using a high-frequency linear transducer (7)(8)(9)(10)(11)(12)(13). The tendon may be conveniently examined in the prone position with the foot over the end of the examination couch.…”
Section: Anatomy and Normal Sonographic Appearancementioning
confidence: 99%